Therapeutic options for advanced thyroid cancer - Apoorva Jayarangaiah; Gurinder Sidhu; Jordonna Brown; Odeth Barrett-Campbell; Gul Bahtiyar; Irini Youssef; Shalini Arora; Samara Skwiersky; Samy I McFarlane (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2019)
Thyroid cancer can be largely classifi ed as well-differentiated, poorly differentiated, medullary and anaplastic. Differentiated thyroid cancer (DTC) includes follicular and papillary subtypes, with the incidence of papillary thyroid cancer (PTC) on the rise. The mainstay of treatment for DTC includes a combination of surgery, radioactive iodine (RAI) and levothyroxine suppression. DTC portends a favorable prognosis, even in the presence of distant metastases, with a 50% rate of 5-year survival largely due to tumor cell's sensitivity to RAI therapy infl uencing disease outcome. In radioactive iodine refractory differentiated thyroid cancer (RAI-refractory DTC) there is a lower survival rate prompting the use of other therapeutic options available.